Povezanost življenjskega sloga žensk s samopregledovanjem dojk - Mlinar, Suzana (Šport (Ljubljana), 2021)
The purpose of the study was to determine the relationship between women’s lifestyle with breast self-examination. Randomly, 255 women were included in the study. Data were collected using an anonymous survey questionnaire that was processed using the IBM SPSS statistical program. In addition to descriptive statistics, we used the chi-square test. Alpha levels of p?0.05 werw considered as significant. 36.9% of respondents were engaged in physical activity that has effects on health, including 54.2% of those living in the city (p=.020), 42.2% with higher level education (p=.048 ), 91.6% of those who eat fruit and vegetables daily (p=.008) and 16.5% of those who self-examine their breasts monthly (p=.011). In 38.9% of respondents who experience stress every day, they engage in physical activity for more than 60 minutes (p=.011). Respondents who consume alcoholic beverages are 87.5% physically active for 40 to 60 minutes (p=.007) and as many as 52.1% drink more than three units of alcohol on special occasions (p=.027). Our findings support the role of physical activity in shaping a healthy lifestyle and regular breast self-examination, which are important factors in empowering women to take care of their own health.
Keywords: alcohol; alkohol; breast cancer; physical activity; rak dojk; sport; stres; stress; šport; telesna dejavnost; women; ženske